2017
DOI: 10.1177/0263617417713573
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative CO2 adsorption promotes high CO2 adsorption density over wide optimal nanopore range

Abstract: Separation of CO2 based on adsorption, absorption, and membrane techniques is a crucial technology necessary to address current global warming issues. Porous media are essential for all these approaches and understanding the nature of the porous structure is important for achieving highly efficient CO2 adsorption. Porous carbon is considered to be a suitable porous media for investigating the fundamental mechanisms of CO2 adsorption, because of its simple morphology and its availability in a wide range of well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 41 publications
3
25
0
Order By: Relevance
“…In fact, the adsorption isotherms obtained from the various pressures and specific temperature explained the equilibrium adsorption capacity of the ACNFs. The isotherms were found to be Type I, being in line with the findings based on N 2 isotherms, i.e., the microporous features that were induced to achieve the high adsorption of CO 2 [ 58 ].…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…In fact, the adsorption isotherms obtained from the various pressures and specific temperature explained the equilibrium adsorption capacity of the ACNFs. The isotherms were found to be Type I, being in line with the findings based on N 2 isotherms, i.e., the microporous features that were induced to achieve the high adsorption of CO 2 [ 58 ].…”
Section: Resultssupporting
confidence: 73%
“…In fact, the adsorption isotherms obtained from the various pressures and specific temperature explained the equilibrium adsorption capacity of the ACNFs. The isotherms were found to be Type I, being in line with the findings based on N 2 isotherms, i.e., the microporous features that were induced to achieve the high adsorption of CO 2 [58]. Table 3 summarized the comparison between CO 2 uptakes by different carbon fibers-based adsorbents and their composites from previous literature with the rGO/ACNF composites produced in this study.…”
Section: Co 2 Adsorption Performancesupporting
confidence: 85%
“…However, CO 2 adsorption decreases to about 5.26 mmol g À1 in MIL-96(Al)-Ca4 because further increasing in Ca 2+ content leads to decrease in the BET surface area, pore-volume, micropore content. 54 It seems that the pore volume expands when the high pressure is applied. Therefore, CO 2 uptake is dramatically increased in the MIL-96(Al)-Ca samples with the Ca 2+ content lower than 0.74%.…”
Section: Co 2 and N 2 Adsorption Behaviormentioning
confidence: 99%
“…Investigation of Chen et al [49] showed that the adsorption of CO 2 molecules in the 0.3 nm slit pores, due to the similar size of CO 2 molecules, was very poor. In contrast, the highest CO 2 adsorption was noticed in the 0.4 nm pores.…”
Section: Discussionmentioning
confidence: 99%